Hyperlipidaemia in paediatric practice. Issue 3 (March 2015) - Dale, Peter; Shortland, Graham J.; Datta, Dev; Cole, Duncan
Abstract: Assessment of hyperlipidaemia in children is important to prevent cardiovascular disease later in life. Secondary causes of hyperlipidaemia should always be considered during clinical assessment. There are several primary causes of primary hyperlipidaemia, of which familial hypercholesterolaemia (FH) is the most important. It is believed that up to 85% of the 120, 000 individuals with FH are currently not identified but the process of cascade testing is likely to identify more children with this important condition in the near future. This process has begun in Wales in 2010 and is due to begin shortly in other areas of the UK. Recent NICE guidelines for the treatment of FH have been produced. These include clear guidance for the diagnosis, management and treatment of children and young people who are diagnosed with this condition. Several classes of drugs are used to treat hyperlipidaemia in children, but the statins are most commonly used. They are effective and safe to use in older children.